The Influence of Product Reviews, Trust, and Marketing Content on Tiktok on Jiniso's Product Purchase Decisions - Tegar Mulya Aji R (PT FORMOSA CENDEKIA GLOBAL, 2023)
Internet users in Indonesia are increasing from year to year, based on a report according to APJII (2022) up to 77.02% of Internet users in Indonesia today, this number has slightly increased compared to the previous year. Along with the increasing number of internet users in Indonesia, there are many applications that are a media tool to find information, one of which is the Tiktok application. The popularity of Tiktok is increasing, predicting that Tiktok has active users reaching 755 million people in 2022, The most popular content on the Tiktok application is about fashion. This study aims to determine the influence of product reviews, trust, and marketing content on Tiktok on purchasing decisions for jiniso products. This study used 4 variants, namely product reviews, trust, marketing content and purchase decisions. The data collection technique used a questionnaire distributed to 100 respondents. The data in this study used primary data with data collection carried out by distributing questionnaires using a 5-point Likert scale by measuring 30 questions. The data is then processed with multiple linear regression methods. The results of this study show that product reviews have a positive effect on purchasing decisions. Trust positively influences purchasing decisions. Content marketing has a positive influence on purchasing decisions. Product reviews, trust, and marketing content on Tiktok affect together or simultaneously on purchasing decisions